2020
DOI: 10.1039/d0qo00827c
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free reductive coupling of aliphatic aldehydes/ketones with 4-cyanopyridines: expanded scope and mechanistic studies

Abstract: An efficient and practical bis(pinacolato)diboron (B2pin2) mediated radical-radical cross-coupling of 4-cyanopyridine with aliphatic aldehydes/ketones has been established. The metal-free protocol features simple and mild reaction conditions, excellent functional group tolerance,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The combined molecular dynamics and coordinated driving method 17 implemented in the Automated Design of Chemical Reactions Program 18 was applied to locate the structures of all minima and transition states. In our previous study, we had already shown that electron-deficient pyridines can react with B 2 pin 2 to furnish pyridine-ligated boryl radical IM1 , 12 which can react with perfluoroalkyl iodides to afford perfluoroalkyl radicals via a bimolecular homolytic substitution (S H 2) reaction. 14 Therefore, we will focus on the reaction between allylbenzene 1a and the perfluoroalkyl radical in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined molecular dynamics and coordinated driving method 17 implemented in the Automated Design of Chemical Reactions Program 18 was applied to locate the structures of all minima and transition states. In our previous study, we had already shown that electron-deficient pyridines can react with B 2 pin 2 to furnish pyridine-ligated boryl radical IM1 , 12 which can react with perfluoroalkyl iodides to afford perfluoroalkyl radicals via a bimolecular homolytic substitution (S H 2) reaction. 14 Therefore, we will focus on the reaction between allylbenzene 1a and the perfluoroalkyl radical in this work.…”
Section: Resultsmentioning
confidence: 99%
“…We showed before that 4-cyanopyridine/B 2 pin 2 can be used as a pyridine-4-yl equivalent in reductive coupling reactions with carbonyl derivatives. 12 When using 1.2 equivalents of the 4-cyanopyridine/B 2 pin 2 combination, the ATRA reaction furnished iodoperfluoroalkylation product 3a in 42% yield along with a slight amount of perfluoroalkylative pyridylation product 3a′ . Since increasing the ratio of 4-cyanopyridine/B 2 pin 2 caused an increase of the concentration of pyridine-boryl radicals, we attributed the low yield of 3a to the occurrence of the competitive cross-coupling reaction ( IM1 + IM2 → 3a′ ) in the presence of stoichiometric 4-cyanopyridine/B 2 pin 2 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Some single nitrogen heterocycles that are used for a variety of organic transformations, including pinacol coupling, are strategically substituted pyridines. [71][72][73][74] The single nitrogen heterocycles are generally para-substituted pyridines with an electron withdrawing group, such as CN or CO 2 Me, and react with B 2 pin 2 to form mono-borylated pyridine-based radicals that deliver a single Bpin substituent. The mono-borylated substituted pyridines may operate via a mechanistic pathway distinct from the diborylated N-heterocycles, providing an opportunity for study of single borylation of nitrogen oxyanion ligands.…”
Section: Frontier Dalton Transactionsmentioning
confidence: 99%
“…Pyridine nucleus and their derivatives are important class of heterocyclic compounds include compounds exhibiting antimicrobial, antihypoxic activity, antiinflammatory, and analgesic [40]. Functionalized pyridines are not only existing in a wide range of bioactive molecules, but also widely used as building blocks that can be transformed into a series of valuable structures in the preparation of ligands and functional materials [41,42].…”
mentioning
confidence: 99%